Examining the role of intrinsic and extrinsic cues from service requirement narratives in web-based time banking participation decisions - Jiao, Huifang; Lin, Meiyan; Ma, Lijun; He, Mei; Yu, Shiguan (Frontiers in Public Health, 2024)
IntroductionTime banking, known as “Community/Neighborhood Pension,” instantiates a form of co-creation that can provide a new solution to fulfil the unmet social service needs of community members with idle resources, which is a feasible solution to alleviate pension pressure. The sustainable operation of time banks relies on the co-creation and active participation of community members. Therefore, in this study, we investigate the motivation of members to participate in web-based time banks from a service requirement narrative perspective.MethodsWe collected data of 21969 service requirement projects from publicly available information on the website of Nansha Timebank (nstimebank.com, a web-based time bank platform in China). Using the data, we built a model to assess how the intrinsic and extrinsic cues underlying service requirement narratives affect the time bank participation decisions of service providers drawing on grounded theory. Then we conducted a regression analysis to test our hypotheses.ResultsWe find that participants respond positively to time coins return and narratives highlighting social connection and value fulfilment but respond negatively to service hour costs and empathy-altruism cues.DiscussionOur findings suggest that people who receive services in web-based time banking platform should utilize different linguistic cues in service requirement descriptions to improve service exchange results.